2022
DOI: 10.3389/fnins.2022.878239
|View full text |Cite
|
Sign up to set email alerts
|

Update to the Treatment of Parkinson’s Disease Based on the Gut-Brain Axis Mechanism

Abstract: Gastrointestinal (GI) symptoms represented by constipation were significant non-motor symptoms of Parkinson’s disease (PD) and were considered early manifestations and aggravating factors of the disease. This paper reviewed the research progress of the mechanism of the gut-brain axis (GBA) in PD and discussed the roles of α-synuclein, gut microbiota, immune inflammation, neuroendocrine, mitochondrial autophagy, and environmental toxins in the mechanism of the GBA in PD. Treatment of PD based on the GBA theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 219 publications
0
14
0
Order By: Relevance
“…Also, decreased abundance of Barnesiella has been previously associated with age-related cognitive decline in mice 66 . Finally, the relative abundance of Barnesiella was shown to correlate with cognitive ability in patients with Parkinson's disease 67,68 , and differentially abundant in mice after induced traumatic brain injury 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, decreased abundance of Barnesiella has been previously associated with age-related cognitive decline in mice 66 . Finally, the relative abundance of Barnesiella was shown to correlate with cognitive ability in patients with Parkinson's disease 67,68 , and differentially abundant in mice after induced traumatic brain injury 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing studies aim to deepen our understanding of the interactions within the microbiome–gut–brain axis, particularly exploring mechanisms between the gastrointestinal tract and the nervous system [ 122 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ]. Future research should focus on more precise analyses and explorations of the composition of gut microbiota, identifying which strains are dominantly associated with conditions such as anxiety, depression, Parkinson’s disease, and other psychiatric and cognitive disorders, including Alzheimer’s disease [ 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 ]. Areas that remain less explored, such as the various negative associations of different bacterial strains, including inflammatory diseases, neuroinflammation, and metabolic disorders or postpartum depression, require further investigation for a deeper understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the gut microbiota is essential for the pathological progress of PD. Analyzing the composition of gut microbiota in PD patients, many studies have demonstrated a decrease in SCFAs-producing bacteria and an increase in proinflammatory bacteria [ 58 , 59 ]. Interestingly, SCFAs can also affect the composition and structure of gut microbiota by modifying intestinal pH, mucosal permeability, mucin synthesis, and intestinal immunity.…”
Section: Scfas and Pd Pathologymentioning
confidence: 99%